GIANT NON-FUNCTIONING ADRENOCORTICAL CARCINOMA (Indonesian Journal of Urology, 2023)
Objective: This study aims to report a case of a 51 year old male who was referred to our Department of Urology and was diagnosed with a nonfunctioning giant ACC. Case(s) Presentation: The case report describes a 51-year-old Indonesian man who presented to our department with complaints of persistent upper left abdomen discomfort, previously misdiagnosed as dyspepsia. He was diagnosed as having non-functioning adrenocortical carcinoma and underwent open adrenalectomy. Discussion: Although the patient is 51 years old and the tumor has grown to a signify cant size, no lymph node involvement or metastases was found and resection margins were found to be negative. In our patient, functional adrenal work-up results were normal. This has led us to suspect a non-functioning adrenal tumor. Metastatic work-up with CT cranial, chest, and bone survey were performed, with negative result. The biopsy result after resection confirmed the diagnosis of ACC. Conclusion: ACC is a rare aggressive tumor, malignant with poor prognosis. In our case, the non-secretory mass was diagnosed late by manifestation of mass effect symptoms in the upper left quadrant of the abdomen and was previously misdiagnosed as symptoms of dyspepsia. The functional work-up of adrenal masses helped in the determination of its non-functional status. Early diagnosis of ACC and early surgical excision helps in improving the overall survival rate of the patient. Keywords: Non-functioning, adrenocortical carcinoma (ACC), adrenalectomy, case report.